(untitled) (Communication & Society, 2002)
One aspect of globalisation is convergence of income, media and technology of countries. Many authors generally expect this convergence to lead to homogeneous consumer behaviour. This convergence thesis is increasingly questioned. With converging national wealth there still is substantial variation of consumer behaviour across nations, which is not disappearing. This article provides evidence of divergence of consumer behaviour rather than convergence, it describes the influence of culture, how cultural variables can explain variance and presents patterns that can help predict the future